Pengukuran Risiko Kerja dan Lingkungan Fisik pada Departemen IT dengan Menggunakan Metode Rapid Office Strain Assessment (ROSA) - Dian Palupi Restuputri; Diana Puspita; Ahmad Mubin (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2019)
The use of computers in PT X, especially in the IT department (Information and Technology) has reached 98% of work activities. In the results of the questionnaire using the Nordic Body Map and interviews with employees, it is known that employees experience back pain by 100%, neck 90%, waist 80%, and eye disorders caused by the physical environment. This study used the Rapid Office Strain Assessment (ROSA) method as a measurement tool. ROSA is a quick analysis to measure work risks associated with computer use and determine the level of change in cases of worker discomfort. The measurement results show the final ROSA score is above 7. This means that IT work facilities are not in accordance with the standards of ergonomics, ROSA, and the Ministry of Health No. 48 of 2016 which is a very risky condition and can reduce work productivity. Proposed improvements to minimize workplace risks and increase productivity include improvements to working facilities such as chairs, document holders and tables, location and position of facilities, improvement of the physical work environment such as temperatures to 18 °C, lighting 350 lux, bright color walls of the room and improving employee work postures.